2006
DOI: 10.1186/bf03352608
|View full text |Cite
|
Sign up to set email alerts
|

Possible TCRM acquisition of the Kilauea 1960 lava, Hawaii: failure of the Thellier paleointensity determination inferred from equilibrium temperature of the Fe−Ti oxide

Abstract: Natural rock samples may not always be the ideal material for the Thellier-type method as they occasionally result in high paleointensities. The Kilauea 1960 lava, Hawaii, is one such example. Several previous studies have suggested that one of the possible causes for this undesirable behavior is an acquisition of thermochemical remanent magnetization (TCRM) during lava formation. In order to examine this possibility quantitatively, equilibrium temperatures of titanomagnetite grains, which are associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 35 publications
3
21
0
Order By: Relevance
“…Indeed, at least some of our susceptibility curves resemble curves measured on synthetic samples of this composition (Ishikawa et al, 1985). Similar χ -T curves have been also reported for some Hawaiian basalts (Kontny et al, 2003;Yamamoto, 2006) where presence of (hemo) ilmenite was demonstrated by microscopic observations. On the other hand, Kosterov (2001) did not observe peaks attributable to (hemo) ilmenite is basalts from Karoo, Parana, and North Atlantic Large Igneous Provinces (LIPs), despite the fact that abundant exsolved titanomagnetite grains, where hemoilmenite should be present in lamellae (cf.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Indeed, at least some of our susceptibility curves resemble curves measured on synthetic samples of this composition (Ishikawa et al, 1985). Similar χ -T curves have been also reported for some Hawaiian basalts (Kontny et al, 2003;Yamamoto, 2006) where presence of (hemo) ilmenite was demonstrated by microscopic observations. On the other hand, Kosterov (2001) did not observe peaks attributable to (hemo) ilmenite is basalts from Karoo, Parana, and North Atlantic Large Igneous Provinces (LIPs), despite the fact that abundant exsolved titanomagnetite grains, where hemoilmenite should be present in lamellae (cf.…”
Section: Discussionsupporting
confidence: 67%
“…Kontny et al (2003) have measured susceptibility and hysteresis loops as a function of temperature for Hawaiian basalts, also of hotspot origin. Additional low-temperature susceptibility data for Hawaiian volcanics have been reported by Yamamoto (2006). The present study thus extends the low-temperature magnetic measurements both in rock composition (andesites rather than basalts) and in tectonic setting (subduction-related volcanics).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The potential for biasing caused by the remanence carriers undergoing chemical changes below their Curie temperature during the original cooling of the unit (and therefore retaining a chemical or thermochemical remanence) is, as for many studies, not so well constrained. The nature of such effects and the extent to which they occur is presently an area of active research (Smirnov and Tarduno, 2005;Draeger et al, 2006;Yamamoto, 2006). Here, we merely point out that the results of the rock magnetic analysis are consistent with the units having acquired a purely thermal remanence.…”
Section: Discussionmentioning
confidence: 56%
“…Coe et al, 1984;Mochizuki et al, 2004), (3) acquisition of thermochemical remanent magnetizations (TCRM) during natural cooling (e.g. Yamamoto et al, 2003;Yamamoto, 2006), and (4) differences in coolingrate between natural and laboratory conditions (e.g. Fox and Aitken, 1980;Chauvin et al, 2005;Bowles et al, 2005;Morales et al, 2006).…”
Section: Thellier Methodsmentioning
confidence: 99%